The percentage of the contribution of some physical characteristics to the achievement of the Javelin Throwing event for the disabled, short statureF40 - Rasheed, M. HamadAfat (International Journal of Psychosocial Rehabilitation, 2020)
As for the methods of scientific research, the Mathematical Movements E Lee A. proficiency in modern methods of qualitative and quantitative analysis in order to reach E Lee to solve the dilemmas and problems of sporting events. Therefore, the trainer is required to have knowledge of a great deal of knowledge related to the training process, provided that it is an aid and not a level of effectiveness in throwing the javelin for the category of short stature (F40), including In it, the study of the special physical properties that are considered a basic rule in all general activities and in the effectiveness of throwing the javelin for the category of short stature (F40) in particular, so the researcher decided to determine the percentage of the contribution of each element with special physical characteristics in achieving the effectiveness of throwing the javelin for the disabled in the category Short stature (F40) To reach the most accurate final results that serve the task of coaches in people who are satisfied with the association with the best levels, the research aims to: 1. Determine the most important special physical characteristics and implement a Javelin Throwing event for people of short stature (Class F40). 2. Determine the percentage of the contribution of some physical characteristics in achieving the effectiveness of the javelin throw for people of short stature (category F40). A- The researcher used the descriptive approach on (8) short stature players (class F40) throwing the javelin, and (4) special physical characteristics were identified (non-explosive strength, distinctive strength, speed, agility, and flexibility) and their representation. Representation (9) of the physical test data, and after data processing and discussion, the following conclusions were reached: The results showed that there are nine models of significant contribution rates of special physical characteristics as requirements for achieving Javelin Throwing for the disabled with short stature (category). And 40), and it was as follows: - The first (vertical jump from movement) relates to measuring the explosive force of the two men; the second (the long jump from stability) relates to measuring the explosive force of the two legs; and the third (throwing a medical ball weighing 3 kg from movement with one hand as possible) relates to measuring the explosive force of the arm. - The fourth (sitting from lying down with the legs straight for (20) seconds) and the fifth (bending and extending the arms (chin) from the tilted prone position in 10 seconds) related to measuring the characteristic force of velocity. - The sixth (holding the stick with the arms outstretched (raising the shoulders high) and flexibility. - The seventh (jogging with a change of direction (9-3-6-3-9 m)) related to agility, the eighth (shuttle jogging (4 × 10 m)) related to agility, and the ninth (slalom between jogging) covered a distance of 10 AD to measure agility. As for the recommendations, they were: 1. The necessity to use the physical tests reached when selecting players to practice javelin throwing activity for people of short stature (F40 class). 2. The necessity to conduct studies similar to the functional variables and other physical characteristics that were not covered in the current study. 3. The necessity of conducting a similar study for the disabled players of short stature (category F40) and for other activities not included in the current study. 4. The necessity of conducting similar studies in other aspects not covered by the current study, in terms of psychological and physical aspects. 5. The necessity for coaches to pay attention to the final results of the study and to develop them when training spear players for the handicapped of short stature (F40 class) beginners.